Implementación de un centro de recreación deportiva en el Valle de los Chillos - Tapia Sarmiento, Carlos Alberto (2012)
This work details the implementation process of a sports center which provides rental of an artificial turf soccer field covered located at Valle de los Chillos. This idea came up for the need of having a place where to play soccer, a place with excellent services, a friendly environment where the rain and the insecurity do not be obstacles to do what most of men like to do. During the last years, we have observed the construction of some new places in big cities where people can recreate and entertain. The Valle de los Chillos is the place which has been chosen for the construction of this project, this place has good conditions for this project. At first the Valle de los Chillos has all the services besides the neighborhoods around it has a high housing index, the roads have paved entrances which permit to offer a place with facilities and easy access…